Trends in Antiparkinsonian Medication Use in New Zealand: 1995–2011 - T. L. Pitcher; M. R. MacAskill; T. J. Anderson (Parkinson's Disease)
Prescribing trends for medications are influenced by development of new drugs, changes in knowledge about efficacy and side effects, and priorities set by funding agencies. Changes in the utilization of antiparkinsonian agents in the outpatient community in New Zealand were investigated by using the national prescription database for the period 1995–2011. The dispensed volumes of antiparkinsonian agents were converted into number of defined daily doses per 1000 inhabitants per day for analysis. Increases in the dispensed volumes of levodopa (77%), amantadine (350%), and catechol-o-methyl transferase inhibitors (326%) occurred during the study period. Conversely, decreases in the dispensed volumes of anticholinergics (48%), selegiline (82%), and dopamine agonists (6.2%) were observed. New Zealand has seen a substantial increase of the amount of levodopa dispensed in the past 17 years. This increase appears to be related to an increase in the number of people taking the medication. We are unable to extrapolate this change to an increase in the prevalence of PD, given levodopa is used in the treatment of a number of medical conditions. The changes in other antiparkinsonian medications largely reflect changes in availability (increases in entacapone and ropinirole) and best practice treatment (declines in anticholinergics, selegiline, and tolcapone).